Faktor - Faktor yang Mempengaruhi Kelainan Refraksi yang Tidak Terkoreksi - Rangga Adhitia Hermawan; M. Wahyu Budiana; Andi Saputra; Guntur Wijaya (Akademi Refraksi Optisi dan Optometry Gapopin, 2023)
The purpose of this study was to find out what factors influence uncorrected refractive errors. This type of research is qualitative research with a literature study method by collecting seven related journals both nationally and internationally. The results of this study indicate that the factors that influence uncorrected refractive errors include socioeconomic status, access to health care, children, gender, and refractive errors.